Gallbladder malignancy an old soul revisited-ultrasonography and contrast enhanced computed tomography evaluation in tertiary care center in South West Bihar - Bhat, Shreya; Ahmad, M. Shamin; Sharma, Sachin; Puja (International Journal of Research in Medical Sciences, 2024)
Background: Gallbladder (GB) malignancy is the commonest biliary tract carcinoma. It ranks fifth among the malignancies of the gastrointestinal tract and in all encompasses about 1-3% of all malignancies. Its peak occurrence is in the 5th decade or older with a female predilection. The most cases of GB malignancy are seen along the Ganga river delta region in India. The median survival rate in GB malignancy is approximately 6 months. Methods: A cross-sectional observational study was conducted in the Department of Radiology, Narayan Medical College and Hospital Sasaram over a period of 12 months from August 2022 to September 2023. A total of 40 patients were included on the basis of signs and symptoms of gallbladder carcinoma and underwent USG and CT scan for preoperative radiological diagnosis, following operation all the resected specimens were sent for histopathological evaluation. The diagnostic accuracies of USG and CT scan were then compared against histopathological diagnosis by using Kappa statistics. Results: In the present study, the mean age of the patients was 60 (range: 40-80 years) with female preponderance. About 40% of the gall-bladder were contracted and reduced in size and 35% large and distended on USG examination, while 45% of the gall-bladder were contracted and reduced in size and 37.5% distended and large on CT examination. Approximately 37.5% had irregularly thickened wall and 25% diffusely thickened wall on USG and 25% of gallbladder wall were diffusely thickened and 45% irregularly thickened on CT scan. The present study showed hepatic parenchymal invasion to be 25% on USG and 37.5% on CT scan. The sensitivity and specificity of USG in diagnosing GB carcinoma were 94.2% and 71.4% respectively. Similarly, the sensitivity and specificity of CT scan in detecting GB carcinoma were 97.1% and 83.3% respectively. The test of agreement (Kappa test) revealed an almost 90% agreement between the two procedures meaning that the two diagnostic modalities are almost comparable in diagnosing gall bladder carcinoma. Conclusions: As the histopathological diagnosis of the present study correlated well with USG and CT scan findings in the diagnosis of gallbladder carcinoma; it can be concluded that both USG and CT scan are useful imaging modalities for diagnosing this disease. However, CT scan is more sensitive and specific in predicting gall bladder carcinoma as compared to USG.